Implementation of Social Studies Curriculum in Junior Secondary Schools in Kogi State: Challenges and Prospects - Momoh, Adamu Akor (Researchparks Publishing, 2023)
The study evaluated the enactment of the Social Studies curriculum in junior secondary schools within Kogi State, specifically highlighting discrepancies between the intended curriculum and its practical application. Two primary research questions and hypotheses were formulated, adopting a descriptive research methodology with a survey design. The participants comprised male and female educators from public secondary schools in Kogi State. Utilising the Taro Yamene method, a sample of 341 Social Studies teachers was drawn from a total population of 2328. Stratified sampling was used in selecting 114 schools from 58;, thereafter, 147 males and 194 females’ teachers were randomly selected. A 22-item rating scale was the major data collection tool, segmented into parts A-E. Data analysis, incorporating mean, standard deviation, and the z-test (with a 0.05 significance level). The study identified critical gaps in curriculum implementation. These encompassed inadequate content selection and sequencing, and a neglect of innovative pedagogical techniques. While foundational social studies concepts were emphasised, cultural values and health issues were sidelined. Factors contributing to these discrepancies included teacher apathy, insufficient oversight by educational inspectors, and subpar introductory strategies to engage students. To bridge these gaps, recommendations included optimising content coverage, providing modern instructional tools, enhancing the learning environment, and mitigating teacher and student absenteeism. Furthermore, curriculum revisions to address societal issues and the consistent use of student-centred teaching methods were advocated. Regular principal oversight was emphasised to ensure effective teaching practices.